Altered Electroencephalographic Activity Associated with Changes in the Sleep-Wakefulness Cycle of C57BL/6J Mice in Response to a Photoperiod Shortening - Rozov, Stanislav V.; Zant, Janneke C.; Gurevicius, Kestutis; Porkka-Heiskanen, Tarja; Panula, Pertti (Frontiers in Behavioral Neuroscience, 2016)
Aim: Under natural conditions diurnal rhythms of biological processes of the organism are synchronized with each other and to the environmental changes by means of the circadian system. Disturbances of the latter affect hormonal levels, sleep-wakefulness cycle and cognitive performance. To study mechanisms of such perturbations animal models subjected to artificial photoperiods are often used. The goal of current study was to understand the effects of circadian rhythm disruption, caused by a short light-dark cycle regime, on activity of the cerebral cortex in rodents. Methods: We used electroencephalogram to assess the distribution of vigilance states, perform spectral analysis, and estimate the homeostatic sleep drive. In addition, we analyzed spontaneous locomotion of C57BL/6J mice under symmetric, 22-, 21-, and 20-h-long light–dark cycles using video recording and tracking methods. Results and Conclusions: We found that shortening of photoperiod caused a significant increase of slow wave activity during non-rapid eye movement sleep suggesting an elevation of sleep pressure under such conditions. While the rhythm of spontaneous locomotion was completely entrained by all light–dark cycles tested, periodic changes in the power of the θ- and γ-frequency ranges during wakefulness gradually disappeared under 22- and 21-h-long light–dark cycles. This was associated with a significant increase in the θ–γ phase-amplitude coupling during wakefulness. Our results thus provide deeper understanding of the mechanisms underlying the impairment of learning and memory retention, which is associated with disturbed circadian regulation.